Criminal Law Policy in Tackling Online Gambling - Cahya Handy Saputra; Muchamad Iksan (Universitas Muhammadiyah Surakarta, 2025)
The transformation of gambling from in-person to online has made it difficult to eradicate completely through existing laws and regulations. This research aims to understand the concept of countermeasures in online gambling crimes within the context of Indonesian criminal law. This research is a normative legal research (juridical normative) that uses secondary data, namely Primary Legal Materials, Secondary Legal Materials. Law enforcement against online gambling crimes in Indonesia involves various integrated legal efforts, both preventively and repressively. Preventive efforts are carried out through prevention policies that focus on improving welfare, legal education, and increasing supervision. Meanwhile, repressive efforts focus on strict actions against the perpetrators, such as blocking online gambling sites, closing the accounts involved, and enforcing criminal sanctions based on various legal regulations, including the Criminal Code, the Electronic Information and Transaction Law, and the Gambling Control Law. there are technical and geographical challenges in law enforcement related to online gambling, synergy between law enforcement officials, internet service providers, and international institutions is needed to increase the effectiveness of handling online gambling cases.